2020
DOI: 10.3389/fpsyg.2020.570565
|View full text |Cite
|
Sign up to set email alerts
|

Small-Group Student Talk Before Individual Writing in Tertiary English Writing Classrooms in China: Nature and Insights

Abstract: When exploring the nature of small-group student talk in English-as-a-foreign-language (EFL) individual writing in terms of what students are talking about, previous studies have mainly linked it to students' writing and focused more on students' written texts than their talk. Consequently, the analyses have largely been text-oriented rather than talk-oriented and have failed to reveal a complete picture of such talk and the socially negotiated nature of the interaction. To fill up the literature gap, we desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 79 publications
4
42
0
Order By: Relevance
“…This inequity in contribution suggests differences in student teachers' inclinations towards group discussion, resulting in interesting interaction patterns. In a sense, some evidence was found that lends support to what has been reported in the literature on classroom interaction discourse (Basturkmen, 2003;Berry, 1981;Li et al, 2020;Stokoe, 2000).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This inequity in contribution suggests differences in student teachers' inclinations towards group discussion, resulting in interesting interaction patterns. In a sense, some evidence was found that lends support to what has been reported in the literature on classroom interaction discourse (Basturkmen, 2003;Berry, 1981;Li et al, 2020;Stokoe, 2000).…”
Section: Discussionsupporting
confidence: 71%
“…Notably, the literature on the nature of talking to learn in higher education has been insufficient (cf. Basturkmen, 2003;Li, Zhang, & Parr, 2020); even less research has focused on talk among student teachers or their interaction patterns in teacher education settings. The available literature has explored talk in the English-for-academic-purposes (EAP) classroom represented by the teacher and students.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the eight teacher participants, 80 second-year students (11 males and 69 females) from the eight teachers’ classes participated in this study voluntarily. They were students in English major and the collection of data from such English-major students was due to the fact that only English-major students are offered English writing course separately in many Chinese universities ( Zhang, 2016 ; Li et al, 2020 ). All these students were Mandarin Chinese speakers and their ages ranged from 19 to 21 with, on average, 11 years of English learning experience.…”
Section: The Studymentioning
confidence: 99%
“…In order to ensure the task difficulty, two measures were adopted. We, firstly, collected writing texts with a same genre, that is, argumentative writing, which is a commonly used assessment for L2 learners’ writing proficiency ( Li et al, 2020 ). In the Chinese tertiary EFL context, students tend to be asked to write argumentative essays in various large-scale standardized English proficiency tests such as IELTS, TOEFL, College English Test Band 4 and 6 (CET-4 and 6), and Test for English Majors Band 4 and 8 (TEM-4 and 8) ( Huang and Zhang, 2020 ).…”
Section: The Studymentioning
confidence: 99%
“…English language education in China has gained its momentum since China adopted the policy of opening to the outside world in the 1980s (Wang and Gao, 2008;Li, 2012). However, Chinese University English teaching has been critiqued for its teacher-centred classrooms and traditional Grammar-Translation teaching methods (Zhang, 2015;Li et al, 2020). In response to this issue, the Chinese Ministry of Education (hereafter MOE), have made massive top-down reforms in advancing English Language Teaching (ELT) at the tertiary level (Zhang and Liu, 2014).…”
Section: Introductionmentioning
confidence: 99%